The Effect of Practice Satisfaction and Practice Immersion on the Problem-Solving Ability of Nursing Students Who Experience Case-Based Extended Reality (XR) Content Learning - Lee, Jong Lan; Park, Sun Jung (Journal of Management World, 2024)
This study aims to understand the effect of practice satisfaction and practice commitment on the problem-solving abilities of nursing students who have experienced learning through case-based extended reality (XR) content. Methods: A descriptive study design was used. The participants were 150 nursing students from various universities in Korea. Data were collected using self-reported questionnaires through a survey. The questionnaire was administered after implementing learner-based case-based extended reality (XR) content. Data were analyzed using multiple linear regression. Multiple linear regression analysis was conducted on the data to examine the effect of learner-based learning through XR content on the nursing students' practice immersion and satisfaction and their impact on the problem-solving abilities. The results showed that practice immersion (t=4.082, p